Polysaccharides From Lentinus Edodes Inhibits Lymphangiogenesis via the Toll-Like Receptor 4/JNK Pathway of Cancer-Associated Fibroblasts - Wang, Yuanyuan; Zeng, Yanqiong; Zhu, Linyu; Wan, Jiajia; Lei, Ningjing; Yao, Xiaohan; Duan, Xixi; Zhang, Yana; Cheng, Yanru; Tao, Ning; Qin, Zhihai (Frontiers in Oncology, 2021)
Polysaccharides from Lentinus edodes (L. edodes) have been successfully used as adjuvant chemotherapy drug to treat lymphatic metastasis in some malignancies, such as colorectal cancer (CRC), lung cancer and gastric cancer. The CRC could metastasize via lymphatic vessels. Lymphatic metastasis is commonly thought to be the cause of poor prognosis of CRC. The mechanism of polysaccharides from L. edodes inhibiting lymphatic metastasis of CRC is still unclear. In this study, we explored how MPSSS, a novel polysaccharide component of L. edodes, influences lymphangiogenesis and lymph node metastasis. The results show that MPSSS can reduce lymphangiogenesis and lymphatic metastasis of CRC in mouse model. And combined with in vitro study, a likely mechanism is that MPSSS reduce the secretion of VEGF-C by cancer associated fibroblasts (CAFs). This effect can be suppressed by a TLR4 inhibitor, which suggests that MPSSS plays a role in CAFs through the TLR4/JNK signaling pathway. In conclusion, MPSSS may reduce lymphangiogenesis by decreasing the VEGF-C secretion of CAFs, which may provide a new strategy for the comprehensive treatment of CRC.